2014
DOI: 10.1007/s00701-014-2240-4
|View full text |Cite
|
Sign up to set email alerts
|

Subdural motor cortex stimulation: feasibility, efficacy and security on a series of 18 consecutive cases with a follow-up of at least 3 years

Abstract: We report an efficacy at least as good as ED MCS, with no complications specific to SD MCS, even with prolonged follow-up. The data are insufficient to actually prove a lower energy use in SD MCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…Risk of bias as assessed by the RoB2 showed that all included papers had a low overall risk-of-bias judgement 47,[75][76][77] . Risk of bias as assessed by the ROBINS-I showed that all included papers had a moderate overall risk-of-bias judgement 9,10,13,24,40,[42][43][44][45]55,[78][79][80][81][82][83][84][85][86] . Table 1 provides an overview of the quality of the evidence of the included papers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Risk of bias as assessed by the RoB2 showed that all included papers had a low overall risk-of-bias judgement 47,[75][76][77] . Risk of bias as assessed by the ROBINS-I showed that all included papers had a moderate overall risk-of-bias judgement 9,10,13,24,40,[42][43][44][45]55,[78][79][80][81][82][83][84][85][86] . Table 1 provides an overview of the quality of the evidence of the included papers, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there was the considerable confusion about the efficacy of MCS because four studies [6, 810] shown the invalid outcomes. Among included literatures, all reported the age of patients and the preoperative VAS scores [10, 11, 1423]; seven reported the duration of the disease [11, 16, 17, 1921, 23]; and 9 reported the time of follow-up [10, 1517, 1923]. All the information used in the present study were available in the Additional file 1.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Delavall ee et al (2014) report pain to be intractable when patients were refractory to ≥2 analgesic medications, had presented neuropathic pain for ≥6 months ranging between 5 and 10 on a scale of 1 to 10, and a NRS score evaluated 4 times a day, and were evaluated by a neurosurgeon, a neurologist, and a psychiatrist. 21 The study by Saitoh et al, 55 however, used a less extensive definition of refractory pain: "patients had been treated with various medications including anticonvulsant and/or antidepressant drugs." To correct for such inconsistencies, and because a previous study found that responsiveness to gabapentin was positively correlated with iMCS outcome, 12 the authors included intake of oral analgesics in their final dataset and NNA.…”
Section: Strengths and Limitationsmentioning
confidence: 99%